HIDDEN ADULT IN OKKY MADASARI’S CHILDREN’S BOOK, MATA DI TANAH MELUS - Ahmad, Ahmad; Kahfi Susanto, Ashabul; Shah, Farooq (Elite : English and Literature Journal, 2022)
Okky Madasari is an Indonesian novelist who is popularly known as a critic who used to voice social criticism through her writings. However, such social criticism appears not only in her adult novels but also in her children’s novels. In 2018, she first published a children’s book entitled Mata di Tanah Melus, a novel that talks about the adventures of Matara, a 12-year-old girl in the land of Melus, East Nusa Tenggara, Indonesia. This novel receives appreciation both from readers and scholars, and some scholars have examined how social criticism is reflected in the novel. However, none have analysed the reason why Madasari urges social criticism in this children’s book. Therefore, this research aims to discuss the complexity of this children’s book and to uncover why social criticism is insisted in Mata di Tanah Melus. This is descriptive analysis research in which the researchers’ attention focuses on the structure of the novel through close reading. Close reading here means the researchers read the novel several times in the way which Perry Nodelman has suggested: “reading as an adult versus reading as a child” in reading children’s fiction. The result shows that Mata di Tanah Melus is too complex for children’s readers. The complexity can be seen from the high-level language as well as the complicated idea of the story. The complicated issues are clearly seen from the way in which the author insists on social criticism as her ideology, as she has always done in her adult novels. Thus, this research is in line with Nodelman’s theory that there is always a hidden adult in children’s novels.